Serotonin – lipid interactions and their role in behavior - Kalinichenko, Liubov; Gulbins, Erich; Kornhuber, Johannes; Müller, Christian P. (Handbook of Behavioral Neuroscience, 2020)
The dysfunction of the serotoninergic system is one of the crucial pathways for the development of psychiatric disorders such as depression, addiction, Alzheimer's and Parkinson's diseases. Many psychiatric drugs act via the interactions with serotonin receptors, transporter, or enzymes. However, current treatment strategies normalizing the functioning of serotoninergic system are characterized by low response rate, delayed effects, and substantial side effects. Thus, new treatment strategies for the modulation of brain serotonin balance are in high demand. Recent studies showed a possible involvement of the compounds of biological membrane lipids, such as cholesterol, sphingolipids, and others, in the regulation of serotonin signaling. Here, we discuss mechanisms of interaction between groups of lipids, which serve as a structural basis for membrane signaling of serotonin. Understanding these mechanisms will allow development of new strategies to indirectly target the serotoninergic system via alteration of lipid composition of membranes. This might improve therapies directed to the restoration of the serotonin balance in the brain.
CRIS-Team Scopus Importer:2020-02-04
Keywords: 5-HT; Ceramide; Cholesterol; Gangliosides; Lipid domains; Lipids; PUFAs; Serotonin; Serotonin receptors